Composition and distribution of Lutjanus johnii and other species using wire traps in the waters of Rigaih, Aceh Jaya Regency - Nasruddin Nasruddin; Mulyono S Baskoro; Roza Yusviandayani; Vita Rumanti Kurniawati; Dahri Iskandar (Depik, 2025)
The catch results show that wire traps are an effective and selective fishing gear for Lutjanus johnii, with a total catch of 244.1 kg. The bycatch, consisting of 10 species, amounted to 208.1 kg, also caught using wire traps in the waters of Rigaih. This study aimed to identify the composition of the bycatch, the ratio between the target catches and the bycatch, and the size range of the dominant bycatch species caught during L. johnii fishing operations in Rigaih waters. The research was conducted in the waters of Rigaih during NovemberDecember 2024 using wire traps (dimensions: length x width x height = 120 x 100 x 75 cm). The results showed that the primary catch using wire traps was dominated by L. johnii, with a total of 135 individuals (48.7%) weighing 244.1 kg. The bycatch amounted to 208.1 kg (46.1%). The bycatch species included Caranx sexfasciatus with 42 individuals (15.2%) weighing 18.4 kg (4.1%), Lutjanus gibbus with 24 individuals (8.7%) weighing 31.9 kg (8.7%), and Epinephelus malabaricus with 24 individuals (8.7%) weighing 114.5 kg (25.3%). The dominant bycatch size classes caught in the wire traps included L. campechanus with a total length range of 1820 cm, L. campechanus with a total length range of 3045 cm, and Epinephelus malabaricus with a total length range of 4075 cm. The proportion of the target catch to bycatch by weight was 53.9% to 46.1%. This means that for every 1 kg of L. johnii caught, approximately 0.85 kg of bycatch was also captured.KeywordsLutjanus johniiwire trapAceh Jayasex ratiofish composition